Graphite phase carbon nitride adsorbent rich in cyano group on surface as well as preparation method and application of graphite phase carbon nitride adsorbent

By introducing alkaline potassium salt into graphite phase carbon nitride adsorbents, regulating its structure and forming cyano functional groups, the problem of insufficient adsorption capacity of existing adsorbents on palladium ions is solved, and a significant improvement in adsorption capacity and the improvement of the stability of the material in an acidic environment is achieved.

CN119746797APending Publication Date: 2025-04-04NANJING UNIV +1

Patent Information

Application Number
CN202411777770.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

When the existing graphite phase carbon nitride adsorbents absorb palladium ions in acidic wastewater, they lack functional groups with special affinity for palladium ions, which limits the increase in adsorption capacity.

Method used

By introducing alkaline potassium salt into the carbon nitride precursor, the structure of the graphite phase carbon nitride is regulated, and the adsorption capacity of the graphite phase is generated is improved.

Benefits of technology

The adsorption capacity of the adsorbent to palladium ions in acidic wastewater has been significantly improved, and the carbon nitride of the original graphite phase has been increased by 1.20 to 1.68 times, and the isoelectric point of the material has been reduced, improving its stability in an acidic environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746797A_ABST
    Figure CN119746797A_ABST
Patent Text Reader

Abstract

The invention discloses a graphite phase carbon nitride adsorbent rich in cyano groups on the surface and a preparation method and application thereof.The preparation method comprises the steps that a precursor of carbon nitride and alkaline potassium salt are dissolved in deionized water respectively, then the precursor of carbon nitride and the alkaline potassium salt are stirred and mixed to be uniform, evaporative crystallization is conducted, and a crystal mixture is obtained; and grinding the crystal mixture, calcining at high temperature, further grinding, washing and drying to obtain the graphite phase carbon nitride adsorbent rich in cyano groups on the surface. The surface electrification and the characteristic functional group type of the graphite phase carbon nitride are regulated and controlled through the alkaline sylvite, the synthesis process is easy and convenient to operate, large-scale production can be achieved, and excellent adsorption performance on palladium ions in acid wastewater is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of adsorption materials, and in particular relates to a graphite phase carbon nitride adsorbent with cyanide-rich surface, and a preparation method and application thereof. Background Art

[0002] Palladium is a rare and precious metal. Due to its excellent physical and chemical properties, it plays an important role in electronics, catalysis, fuel cells, and pharmaceuticals. However, the acidic palladium-containing wastewater discharged by these industries during the production process not only wastes precious palladium resources, but also has toxic effects on aquatic and terrestrial organisms. Therefore, recovering palladium from highly acidic wastewater has become an important research direction in the fields of environmental protection and resource recycling. Currently known methods for treating acidic palladium-containing wastewater include chemical precipitation, ion exchange, reverse osmosis, solvent extraction, and adsorption. Among the above methods, the adsorption method is low-cost, easy to operate, and environmentally friendly, and is an ideal method for recovering palladium from acidic wastewater.

[0003] In recent years, graphite carbon nitride (g-C3N4) has attracted widespread attention in the field of adsorption due to its simple preparation process, easy modification, and tolerance to strong acids and bases. In addition, by adjusting the pore structure of g-C3N4, its specific surface area can be effectively increased, thereby enhancing its adsorption capacity. Unfortunately, g-C3N4 does not have functional groups with special affinity for palladium ions, and the method of introducing specific functional groups on its surface is complicated, which limits the further improvement of adsorption capacity. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a surface cyanide-rich graphite phase carbon nitride adsorbent that can efficiently recover metals and adsorb palladium ions in acidic wastewater; another purpose of the present invention is to provide a preparation method and application of the surface cyanide-rich graphite phase carbon nitride adsorbent.

[0005] Technical solution: The graphite phase carbon nitride adsorbent with cyanide-rich surface of the present invention has a surface rich in cyanide functional groups (-C≡N).

[0006] Preferably, the adsorption capacity of the surface cyanide-rich graphite-phase carbon nitride adsorbent for palladium ions is 2.60 to 3.62 mg / g, which is 1.20 to 1.68 times higher than that of the original graphite-phase carbon nitride.

[0007] Preferably, compared with the isoelectric point of 4.85 of the original graphite phase carbon nitride, the isoelectric point of the surface cyanide-rich graphite phase carbon nitride adsorbent is significantly lower, approximately in the pH range of 2.20 to 2.50. And by adjusting the type of alkaline potassium salt, the surface of the material can be negatively charged.

[0008] The preparation method of the graphite phase carbon nitride adsorbent with rich cyanide groups on the surface of the present invention comprises the following steps: dissolving a carbon nitride precursor and an alkaline potassium salt in deionized water respectively, stirring and mixing the two evenly, evaporating and crystallizing to obtain a crystalline mixture; grinding the crystalline mixture and calcining it at high temperature, further grinding it, washing it, and drying it to obtain the graphite phase carbon nitride adsorbent with rich cyanide groups on the surface.

[0009] Preferably, the mass ratio of the alkaline potassium salt to the carbon nitride precursor is (0.5-2):(100-200).

[0010] Preferably, the precursor of the carbon nitride is urea.

[0011] Preferably, the alkaline potassium salt is at least one of potassium bicarbonate, potassium carbonate and potassium hydroxide.

[0012] Preferably, the concentrations of the carbon nitride precursor and the alkaline potassium salt in deionized water are 0.005-0.025 g / mL and 1-2.5 g / mL, respectively.

[0013] Preferably, the stirring and mixing time is 10 to 30 minutes.

[0014] Preferably, washing is performed until the pH of the carbon nitride is 6.8 to 7.2, and then drying is performed at 50 to 70° C. for 10 to 14 hours.

[0015] Preferably, the washing solvent is deionized water.

[0016] Preferably, the temperature of the evaporation crystallization is 50-70°C.

[0017] Preferably, the evaporation crystallization time is 18 to 24 hours.

[0018] Preferably, the grinding time before the high-temperature calcination is 10 to 30 minutes.

[0019] Preferably, the high-temperature calcination is carried out in a muffle furnace, and the treatment procedure of the high-temperature calcination is: heating to 500-600° C. at a heating rate of 2-10° C. / min, and then calcining at 500-600° C. for 3-5 hours.

[0020] Preferably, the grinding time after high-temperature calcination is 10 to 30 minutes, and the obtained material needs to pass through a 100-mesh sieve.

[0021] The invention discloses an application of the graphite-phase carbon nitride adsorbent with rich cyanide groups on its surface in metal resource recovery.

[0022] Preferably, the metal resource is palladium ions.

[0023] The specific steps of metal resource recovery include: preparing acidic palladium-containing wastewater as a treatment object, wherein the palladium ion concentration is 1-10 mg / L and the acidity is 0.1-5 mol / L, and adding 10-50 mg of the surface cyanide-rich graphite phase carbon nitride adsorbent of the present invention. Oscillating at 20-30° C. and 160-200 rpm for 10-15 hours, an adsorption experiment is performed. After the adsorption reaction starts, 1-2 mL of samples are taken at intervals, and after the samples are filtered through a filter membrane, the concentration of palladium ions in the solution is determined using an inductively coupled plasma mass spectrometer (ICP-MS) to calculate the adsorption capacity.

[0024] Principle of the invention: The current method of introducing specific functional groups on the surface of materials usually involves complex chemical or physical processes, and also requires the use of chemical reagents such as strong acids, strong bases or organic solvents, which is not only cumbersome to operate, but also poses a risk of secondary pollution. In addition, the introduced functional groups may not be stable enough in practical applications, and are easily decomposed or lose activity under environmental conditions, which limits the service life and effect of the material. The present invention achieves the regulation of material structure by introducing alkaline potassium salts into carbon nitride precursors. Potassium bicarbonate, potassium carbonate or potassium hydroxide is used as a graphite phase carbon nitride structure regulator, which is completely dissolved in water and stirred and mixed with a urea solution, and evaporated and crystallized to obtain a carbon nitride precursor. A high-temperature calcination method can be used to synthesize a graphite phase carbon nitride material with structure regulation in one step. In this process, the introduction of alkaline potassium salts can change the pH value of the polymerization reaction, and affect the thermal decomposition and polymerization of urea molecules, thereby changing the crystallinity and functional group types of polymerized carbon nitride. This structural regulation method can simultaneously change the charged type on the adsorbent surface and generate cyano (-C≡N) functional groups during the synthesis process. This functional group has a specific adsorption capacity for palladium ions, thereby improving the adsorption efficiency of the adsorbent for palladium ions in acidic wastewater, which is of great significance for improving the adsorption capacity of the material for palladium ions.

[0025] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0026] (1) The graphite-phase carbon nitride adsorbent with a cyanide-rich surface of the present invention produces a cyanide (-C≡N) functional group with a special affinity for palladium ions, thereby improving its adsorption capacity for palladium ions in acidic wastewater; it fills the gap in the current carbon nitride adsorption and recovery of metal ions, and expands its application in the field of resource recovery.

[0027] (2) The present invention introduces alkaline potassium salt into the precursor, thereby regulating the structure of carbon nitride in one step during the high-temperature calcination process to produce a cyano (-C≡N) functional group. Compared with the chemical chelation method for introducing specific functional groups, the present invention not only has a simple synthesis method, but also can simultaneously introduce the cyano (-C≡N) functional group during the carbon nitride synthesis process, and also reduces the use of chemical reagents, thereby reducing the risk of secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 X-ray diffraction patterns of the adsorbent provided in Comparative Example 1 of the present invention and the graphite-phase carbon nitride adsorbent with rich cyanide groups on the surface provided in Examples 1-3;

[0029] Figure 2 Zeta potential diagram of the adsorbent provided in Comparative Example 1 of the present invention and the graphite-phase carbon nitride adsorbent with rich cyanide groups on the surface provided in Examples 1-3;

[0030] Figure 3 Infrared spectra of the adsorbent provided in Comparative Example 1 of the present invention and the graphite-phase carbon nitride adsorbent with rich cyanide groups on the surface provided in Examples 1-3;

[0031] Figure 4 A comparison diagram of the effect of adsorbing palladium ions by the graphite-phase carbon nitride adsorbent with a surface rich in cyanide provided in Example 1 of the present invention and the adsorbent provided in Comparative Example 1;

[0032] Figure 5 A comparison chart of the effects of the graphite-phase carbon nitride adsorbent with a surface rich in cyanide groups provided in Example 2 of the present invention and the adsorbent provided in Comparative Example 1 on adsorbing palladium ions;

[0033] Figure 6 A comparison chart of the effects of the graphite-phase carbon nitride adsorbent with a surface rich in cyanide groups provided in Example 3 of the present invention and the adsorbent provided in Comparative Example 1 on adsorbing palladium ions;

[0034] Figure 7 A comparison diagram of the effect of adsorbing palladium ions by the graphite-phase carbon nitride adsorbent with rich cyanide groups on the surface provided by Examples 1-3 of the present invention;

[0035] Figure 8 This is a comparison chart of the adsorption effects of palladium ions by the graphite-phase carbon nitride adsorbent with surface cyanide-rich provided in Examples 3-5 of the present invention and the adsorbent of Comparative Example 1. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0037] Example 1

[0038] This embodiment provides a graphite-phase carbon nitride adsorbent with a surface rich in cyanide groups, which is prepared by the following method:

[0039] 150g of urea and 1g of potassium bicarbonate were dissolved in 100mL of deionized water respectively, and then the two were stirred and mixed for 20min, and evaporated and crystallized at 60°C to obtain a crystalline mixture; the crystalline mixture was ground for 20min and placed in a muffle furnace, heated to 550°C at a heating rate of 5°C / min, and then calcined at 550°C for 4h; after calcination, it was ground and then washed with deionized water to a pH of 7.0, and then dried at 60°C for 12h to obtain a graphite phase carbon nitride adsorbent with surface rich cyanide.

[0040] Example 2

[0041] This embodiment provides a graphite-phase carbon nitride adsorbent with a cyanide-rich surface. The difference from Example 1 is that 1 g of potassium bicarbonate is replaced by 1 g of potassium carbonate, and the other preparation steps are the same as those of Example 1.

[0042] Example 3

[0043] This embodiment provides a graphite-phase carbon nitride adsorbent with a cyanide-rich surface. The difference from Example 1 is that 1 g of potassium bicarbonate is replaced by 1 g of potassium hydroxide, and the other preparation steps are the same as those of Example 1.

[0044] Example 4

[0045] This embodiment provides a graphite-phase carbon nitride adsorbent with a surface rich in cyanide groups, which is prepared by the following method:

[0046] 200 g of urea and 0.5 g of potassium hydroxide were dissolved in 80 mL of deionized water respectively, and then the two were stirred and mixed for 30 minutes, and evaporated and crystallized at 70°C to obtain a crystalline mixture; the crystalline mixture was ground for 30 minutes and placed in a muffle furnace, heated to 600°C at a heating rate of 10°C / min, and then calcined at 550°C for 5 hours; after calcination, it was ground and then washed with deionized water to a pH of 7.2, and then dried at 70°C for 10 hours to obtain a graphite phase carbon nitride adsorbent with a surface rich in cyanide.

[0047] Example 5

[0048] This embodiment provides a graphite-phase carbon nitride adsorbent with a surface rich in cyanide groups, which is prepared by the following method:

[0049] 100 g of urea and 2 g of potassium hydroxide were dissolved in 90 mL of deionized water respectively, and then the two were stirred and mixed for 10 minutes, and evaporated and crystallized at 50°C to obtain a crystalline mixture; the crystalline mixture was ground for 10 minutes and placed in a muffle furnace, heated to 500°C at a heating rate of 2°C / min, and then calcined at 550°C for 3 hours; after calcination, it was ground and then washed with deionized water to a pH of 6.8, and then dried at 50°C for 14 hours to obtain a graphite phase carbon nitride adsorbent with a surface rich in cyanide.

[0050] Comparative Example 1

[0051] This embodiment provides a carbon nitride, which is different from Embodiment 1 in that potassium bicarbonate is not added, and other operation steps are the same as those of Embodiment 1.

[0052] Application Example 1

[0053] Experiment on the effect of adsorption of palladium ions

[0054] First, 50 mL of acidic palladium-containing wastewater was prepared, wherein the palladium ion concentration was 5 mg / L and the acidity was 1 mol / L, and 25 mg of the surface cyanide-rich graphite phase carbon nitride adsorbent provided in the above-mentioned Examples 1-3 and the carbon nitride provided in Comparative Example 1 were added respectively. The adsorption experiment was carried out at 25 ° C and 180 rpm for 12 hours. After the adsorption reaction started, 1 mL was sampled at 0, 10, 20, 30, 40, 60, 120, 240, 480 and 720 min time points, and the sample was filtered through a 0.22 μm filter membrane. The concentration of palladium ions in the solution was determined using an inductively coupled plasma mass spectrometer (ICP-MS) to calculate the adsorption capacity.

[0055] Application Example 2

[0056] Prepare 50 mL of acidic palladium-containing wastewater, in which the palladium ion concentration is 5 mg / L and the acidity is 1 mol / L, and add 25 mg of the surface cyanide-rich graphite phase carbon nitride adsorbent provided in the above Examples 3-5 and the carbon nitride provided in Comparative Example 1 respectively. Oscillate at 25 ° C and 180 rpm for 12 hours to perform an adsorption experiment. After the adsorption reaction starts, 1 mL is sampled at 720 min. After the sample is filtered through a 0.22 μm filter membrane, the concentration of palladium ions in the solution is determined using an inductively coupled plasma mass spectrometer (ICP-MS), and the adsorption capacity is calculated.

[0057] Figure 1 X-ray diffraction (XRD) diagrams of Comparative Example 1 and Examples 1-3. It is found from the diagram that the material has two characteristic diffraction peaks at 13.1° and 27.6°, which belong to the (100) and (002) crystal planes of graphite phase carbon nitride, indicating that the basic crystal structure of carbon nitride is retained by regulating the structure with alkaline potassium salt; while the diffraction peak intensity of the (100) crystal plane of Examples 1-3 is weakened, indicating that the degree of order of the structure is reduced, which is related to the production of cyano (-C≡N) functional groups by structural regulation.

[0058] Figure 2 The zeta potential diagrams of comparative example 1 and examples 1 to 3 are shown in FIG. From the diagram, it can be found that compared with comparative example 1, the isoelectric points of examples 1 to 3 are significantly lower, and the surface of example 3 is negatively charged within the tested pH range.

[0059] Figure 3 The Fourier transform infrared spectra (FTIR) of comparative example 1 and examples 1-3 are shown in the figure. It can be found from the figure that after the structure is regulated by alkaline potassium salt, the peaks of examples 1-3 at 2175 cm -1 A new absorption peak is generated at , corresponding to the generation of cyano (-C≡N) functional group, indicating the success of structural regulation.

[0060] Figure 4 The graphs are for the palladium ion adsorption capacity of comparative example 1 and example 1. From the graph, it can be found that after potassium bicarbonate is used to regulate the graphite phase carbon nitride structure, the adsorption capacity is increased by 1.20 times.

[0061] Figure 5 The graphs are for the palladium ion adsorption capacity of comparative example 1 and example 2. From the graph, it can be found that after potassium carbonate is used to regulate the graphite phase carbon nitride structure, the adsorption capacity is increased by 1.31 times.

[0062] Figure 6 The graphs are for the palladium ion adsorption capacity of Comparative Example 1 and Example 3. From the graph, it can be found that after potassium hydroxide is used to regulate the graphite phase carbon nitride structure, the adsorption capacity is increased by 1.68 times.

[0063] Figure 7 The graph is a graph of the palladium ion adsorption capacity of Examples 1 to 3. From the graph, it can be found that after potassium hydroxide is used to regulate the structure, the adsorbent has the best adsorption capacity.

[0064] Figure 8 The graphs are for the palladium ion adsorption capacity of comparative example 1 and examples 3 to 5. It can be seen from the graph that adjusting the mass and volume of urea, potassium hydroxide and deionized water can significantly increase the adsorption capacity, proving that the method of using graphite phase carbon nitride with alkaline potassium salt structure is universal.

Claims

1. A graphite-phase carbon nitride adsorbent having a cyanide-rich surface, characterized in that: The graphite phase carbon nitride surface of the adsorbent is rich in cyano functional groups.

2. A method for preparing the graphite-phase carbon nitride adsorbent with surface cyanide-rich as claimed in claim 1, characterized in that: The method comprises the following steps: dissolving a carbon nitride precursor and an alkaline potassium salt in deionized water respectively, stirring and mixing the two evenly, evaporating and crystallizing to obtain a crystalline mixture; grinding the crystalline mixture and then calcining it at high temperature, further grinding it, washing it, and drying it to obtain a graphite phase carbon nitride adsorbent with a cyanide-rich surface.

3. The method for preparing the graphite-phase carbon nitride adsorbent having a surface cyanide-rich structure according to claim 2, characterized in that: The mass ratio of the alkaline potassium salt to the carbon nitride precursor is (0.5-2): (100-200).

4. The method for preparing the surface cyanide-rich graphite phase carbon nitride adsorbent according to claim 2, characterized in that: The precursor of the carbon nitride is urea.

5. The method for preparing the graphite-phase carbon nitride adsorbent having a surface cyanide-rich structure according to claim 2, characterized in that: The alkaline potassium salt is at least one of potassium bicarbonate, potassium carbonate and potassium hydroxide.

6. The method for preparing the surface cyanide-rich graphite phase carbon nitride adsorbent according to claim 2, characterized in that: The concentrations of the carbon nitride precursor and the alkaline potassium salt in deionized water are 0.005-0.025 g / mL and 1-2.5 g / mL respectively.

7. The method for preparing the graphite-phase carbon nitride adsorbent having surface cyanide-rich groups according to claim 2, characterized in that: The stirring and mixing time is 10 to 30 minutes.

8. The method for preparing the graphite-phase carbon nitride adsorbent having surface cyanide-rich groups according to claim 2, characterized in that: Wash until the pH of the carbon nitride is 6.8-7.2, and then dry at 50-70°C for 10-14h.

9. Use of the graphite-phase carbon nitride adsorbent with a surface cyanide group-rich as claimed in claim 1 or the graphite-phase carbon nitride adsorbent with a surface cyanide group-rich as prepared by any one of the preparation methods of claims 2 to 8 in metal resource recovery.

10. The use according to claim 9, characterized in that: The metal resource is palladium ions.

Citation Information

Patent Citations

  • Method for preparing C3N4 material with N defects and application

    CN104787734A

  • Salt-assisted preparation method of three-dimensional graphite phase carbon nitride containing cyano groups

    CN107473191A

  • Pd / crystallized carbon nitride heterojunction photocatalyst, preparation method thereof and application of photocatalytic Ullmann coupling reaction

    CN108452821A

  • Preparation method of palladium ion adsorption material and product of preparation method

    CN110394146A

  • Defect-state carbon nitride material and preparation method and application thereof

    CN110975917A

Cited By

  • Layered double hydroxide modified cyano carbon nitride composite material, preparation method and water pollution treatment method

    CN121513938A